Primary mucinous cystadenocarcinoma of the spleen: a case report and literature review - Zhou, Bo; Zhan, Canyang; Yan, Sheng (Frontiers in Medicine, 2025)
BackgroundTumors of the spleen are uncommon, and most represent metastases from primary organs. Primary mucinous cystadenocarcinoma of the spleen is an extremely rare tumor. Only 11 cases have been reported in the literature.Case presentationHerein, we present a case of primary mucinous cystadenocarcinoma in the spleen in a 50-year-old woman. Abdominal CT and MRI revealed a 9.5 × 6.5 cm mixed solid-cystic lesion with heterogeneous enhancement of the mural nodules and septations, with secondary extension abutting the gastric fundus and pancreatic tail. Notably, tumor biomarker profiling demonstrated remarkable increases in CA19-9 (>12,000 U/ml) and CEA (41.5 ng/ml) levels. Following splenectomy, histopathology revealed the mass to be a mucinous cystadenocarcinoma. Given that metastatic cystadenocarcinoma is relatively common, investigations were performed to evaluate the primary site of malignancy. A whole-body PET-CT scan did not reveal any metabolically active lesions in any part of the body. Neither upper gastrointestinal endoscopy nor colonoscopy revealed any primary malignant lesions. Hence, it was reported as a primary mucinous cystadenocarcinoma of the spleen.ConclusionThe need for presenting this case is due to its rarity and because mucinous cystadenocarcinoma can be a rare differential diagnosis in cases of malignant splenic cysts.